On some minuscule spiders (Araneae: Theridiosomatidae, Symphytognathidae) from the Chocó region of Ecuador with the description of ten new species - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2017)
The spider families Theridiosomatidae and Symphytognathidae found in the Chocó region of Ecuador are examined, a total of 16 and 69 adult specimens were collected respectively in a series of expeditions. In the family Theridiosomatidae, eight new species are described in four different genera; Chthonos kuyllur n. sp.; Naatlo mayzana n. sp.; Ogulnius laranka n. sp., O. paku n. sp.; Theridiosoma ankas n. sp., T. esmeraldas n. sp., T. kullki n. sp., and T. sacha n. sp. We present the first record of the family Symphytognathidae for Ecuador with the description of two new species in two different genera: Anapistula equatoriana n. sp. and Symphytognatha cabezota n. sp.